(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Tuberculosis (TB) is an infectious disease inducing a state of chronic inflammation which could affect the haemostatic mechanism as part of host defences against infection. Proper diagnosis and monitoring of tuberculosis patients undergoing therapy is still a challenge especially in a poor resource country such as Nigeria. This study aims to assess some haemostatic indices of tuberculosis patients and their possible use as markers in monitoring response to anti-tuberculosis treatment. One hundred and twenty TB patients aged 15-60 years and 120 apparently healthy (control) subjects age and gender-matched were studied. Demographic/bio data was compiled by interview and from patients’ case notes. Diagnosis of TB was by sputum smear microscopy, radiography and clinical assessment. Platelet count (PLT), platelet factor 4 (PF4), prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin clotting time (TCT) and fibrinogen (FIB) were determined using standard techniques. The platelet factor 4, prothrombin time, activated partial thromboplastin time and fibrinogen levels of TB patients were significantly higher while the thrombin clotting time was significantly lower (P<0.05) when compared with healthy subjects. While PF4, TCT and FIB improved significantly (P<0.05) as anti-tuberculosis therapy progressed, PLT, PT and APTT remained the same. It is concluded that abnormal activation of haemostasis occurs in TB condition thus pre-disposing TB patients to bleeding complications. Furthermore, platelet factor 4, thrombin clotting time and fibrinogen improved as therapy progressed and therefore may be used as markers for monitoring response to anti-tuberculosis therapy.